Evaluation of Enhanced Recovery After Surgery (ERAS) Protocols in Abdominal Surgery - Sai Mrudula Katikam; Lokesh Kumar Komari; Sai Bhaskar Rayudu Parimi (Journal of Pharmacy and Bioallied Sciences)
Background: Patients having abdominal procedures might benefit from Enhanced Recovery After Surgery (ERAS) protocols, which are a comprehensive approach to perioperative care intended to reduce surgical stress, speed recovery, and enhance overall results. Throughout the preoperative, intraoperative, and postoperative stages, these evidence-based methods prioritize patient-centered, interdisciplinary approaches. The effectiveness of ERAS protocols in elective abdominal operations is assessed in this research in comparison to standard care. Materials and Methods: In total, 150 patients scheduled for elective abdominal procedures participated in a prospective randomized research. They were divided into two groups: 75 patients in the ERAS protocol group and 75 patients in the standard treatment group. While the conventional group got standard treatment procedures, the ERAS group received interventions such as early mobilization, opioid-sparing analgesia, preoperative carbohydrate loading, and early enteral feeding. Postoperative complication rates, duration of hospital stay, and recovery of bowel function were the main outcomes. Readmission rates and patient satisfaction were secondary objectives. Independent t-tests and Chi-square tests were used to examine the data, with a significance level of P < 0.05. Results: The average hospital stay for patients in the ERAS group was shorter (4.6 ± 1.1 days) than that of patients in the traditional treatment group (7.9 ± 2.3 days, P < 0.001). The ERAS group recovered their bowel function in 2.3 ± 0.8 days, which was considerably faster than the traditional group (4.1 ± 1.5 days, P < 0.001). The ERAS group had less postoperative complications (10%) than the traditional group (28%, P = 0.02). Furthermore, compared to 80% in the traditional group, 95% of patients in the ERAS group had good satisfaction levels (P = 0.03). Conclusion: By decreasing hospital stays, speeding the return of bowel function, and increasing patient satisfaction while lowering complications, ERAS procedures dramatically improve recovery in elective abdominal surgery. These results lend credence to the idea that ERAS should be included into standard surgical procedures in order to improve patient outcomes. Its usefulness in other surgical fields should be investigated in future studies.